Effect of Total Assets, Capital Expenditure, Leverage, And GRDP to the Ratio of Regional Financial Independence in Nusa Tenggara Barat Province in 2018-2022 - Muhammad Syafiuddin; Muaidy Yasin; Adhitya Bagus Singandaru (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study examines the effect of total assets, capital expenditure, leverage and PDRB on the ratio of district financial independence in NTB province in 2018-2022. Fiscal decentralization encourages to implement regional autonomy policies, namely giving authority to local governments to regulate finances in their respective regions. Tests were conducted on all districts in NTB province during 2018-2022. The results of this study indicate that total assets, capital expenditure and leverage have no significant effect on the financial independence of districts in NTB province. While PPDRB has a significant effect on the financial independence of districts in NTB province. The research findings indicate that the many or few assets owned by a region will not always affect regional financial independence, the allocation of inappropriate capital expenditures causes regional financial independence to decrease, and the use of capital expenditures to increase regional financial independence. total debt to equity ratio not used wisely, causing the level of regional financial independence to be low. The implications of this research provide warning signals to local governments to be more productive in managing regional wealth assets, allocating capital expenditures in accordance with the budget and on target, and more wisely in using capital expenditures debt to equity ratio local governments in order to increase regional financial independence.